IDENTIFIKASI KEASLIAN KARYA SENI RUPA DENGAN TEKNOLOGI IMAGE PROCESSING BERDASARKAN DETEKSI WARNA DAN TEKSTUR - Ari Purno Wahyu; Kaffah Imanuddin M R Santosa (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
A work of art is a result of someone's thoughts in creating a form of object or art, the work is not just an object and can be in the form of creative ideas and educational concepts that are useful for human lives, the development of the digital world today has a positive impact and negative, for example someone can easily take other people's art works or ideas without credit or granting permission from intellectual property or intellectual property rights, but this does not matter if the art form is released by the art maker and is allowed to be distributed, to overcome With this identification system, the identification of works of art can be done by identifying textures, which in detail can read the most important parts of the painting or work of art by reading pixels and text. color position.